2014
DOI: 10.1021/ol501143c
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Enantioselective Silylation of N-Sulfonylimines: Asymmetric Synthesis of α-Amino Acids from CO2 via Stereospecific Carboxylation of α-Amino Silanes

Abstract: A catalytic enantioselective silylation of N-tert-butylsulfonylimines using a Cu-secondary diamine complex was demonstrated. The resulting optically active α-amino silanes could be carboxylated under a CO2 atmosphere (1 atm) to afford the corresponding α-amino acids in a stereoretentive manner. This two-step sequence provides a new synthetic protocol for optically active α-amino acids from gaseous CO2 and imines in the presence of a catalytic amount of a chiral source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
41
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(44 citation statements)
references
References 71 publications
0
41
0
2
Order By: Relevance
“…[9,10] The starting enantioenriched N-tert-butylsulfonyl--amido silanes 1 can be synthesized either from Ellman's chiral sulfinyl imines by diastereoselective silylation [11] followed by oxidation or from sulfonyl imines by Cu(I)-catalyzed enantioselective silylation recently developed by our group. [10] In contrast, the use of NBoc--amido silanes 1b under the same conditions gave racemic compounds, [12] suggesting that the Boc substitution enhances carbanion generation, whereas the sulfonyl group might stabilize a fluorosilicate intermediate in the stereoretentive transformation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[9,10] The starting enantioenriched N-tert-butylsulfonyl--amido silanes 1 can be synthesized either from Ellman's chiral sulfinyl imines by diastereoselective silylation [11] followed by oxidation or from sulfonyl imines by Cu(I)-catalyzed enantioselective silylation recently developed by our group. [10] In contrast, the use of NBoc--amido silanes 1b under the same conditions gave racemic compounds, [12] suggesting that the Boc substitution enhances carbanion generation, whereas the sulfonyl group might stabilize a fluorosilicate intermediate in the stereoretentive transformation.…”
mentioning
confidence: 99%
“…[16] This result suggested that the present nucleophilic addition proceeded in a retentive manner similar to the case of carboxylation of 1a. [10] One of the diastereomers of 2a (more polar product on silica gel column chromatography) derived from benzaldehyde as well as 2c (less polar product on silica gel column chromatography) derived from cyclohexanecarboxaldehyde For internal use, please do not delete. Submitted_Manuscript were both (S,S)-syn-diastereomers based on comparison of their NMR spectra and optical rotation values with the reported data ( Figure 6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…α-Halonitriles and sulfonyl halides are fast radical generators which have much faster initiation rate than propagation. They have been employed in the ATRP of acrylonitrile 15 , styrene 16 and acrylates 17 . …”
Section: Initiatorsmentioning
confidence: 99%
“…The polymerization had a controlled manner and the PDI is less than 1.5. In the same year, Percec et al also published the ATRP of styrene using the same catalytic system, and the initiator was changed to arylsulfonyl chloride 16 . ATRP of MMA was achieved by using the 2-pyridinecarbaldehyde imine copper(I) complexes and an alkyl bromide as the initiator 28 .…”
Section: Transition Metal Complexesmentioning
confidence: 99%